High-frequency short-pulsed metal plasma-immersion ion implantation using filtered DC vacuum-arc plasma; Part 1; IFOST 2012; Vol. 2 - Ryabchikov A. I. Aleksandr Ilyich; Stepanov I. B. Igor Borisovich; Sivin D. O. Denis Olegovich; Dektyarev S. V. Sergey Valentinovich; Dodorin K. Yu. (2012, 2012)
An innovative concept in the development of advanced coating deposition and ion implantation method including an application of filtered DC metal plasma source and high-frequency short-pulsed negative bias voltage with a duty factor in the range 10 ÷ 99% are considered. The regularities of ion implantation and metal plasma deposition for metal samples are theoretically and experimentally investigated. Experimentally has been shown that metal plasma based ion implantation as well as high-concentration metal plasma ion implantation with compensation of ion surface sputtering by metal plasma deposition as well as ion-assisted coating deposition can be realized by variation of bias potential ranging from 0 V to 4 kV, pulse repetition rate smoothly adjusted in the range (2 ÷ 4.4)×105 p.p.s. and pulse duration ranging from 0,5 to 2 μs. Special features of the material treatment method depending on plasma concentration, pulse repetition rate and duty factor has been examined.